1996
DOI: 10.1152/ajpcell.1996.271.2.c605
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-induced increase in the abundance of Na+ channel subunits

Abstract: The highly selective, amilorideblockable Na+ channel is a major target to the natriferic action of the mineralocorticoid aldosterone. This rat epithelial Na+ channel (rENaC) has been recently cloned from colon and is composed of three homologous subunits denoted alpha-, beta-, and gamma-rENaC (C. M. Canessa, L. Schild, G. Buell, B. Thorens, L. Gautschi, J.-D. Horisberger, and B. C. Rossier. Nature Lond. 367: 463-467, 1994). We have tested the effects of corticosteroids on the abundance of mRNA coding for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
169
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(189 citation statements)
references
References 12 publications
19
169
1
Order By: Relevance
“…ENaC is a heterotrimer of α, β, and γ subunits, all of which are essential for channel functionality 30. The main target of MR in the kidneys is α‐ENaC, whereas in the intestine, β‐ and γ‐ENaC are the main targets 31, 32, 33. The reduction in β‐ and γ‐ENaC but not α‐ENaC expression in the colons of IEC‐MR‐KO mice was consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 88%
“…ENaC is a heterotrimer of α, β, and γ subunits, all of which are essential for channel functionality 30. The main target of MR in the kidneys is α‐ENaC, whereas in the intestine, β‐ and γ‐ENaC are the main targets 31, 32, 33. The reduction in β‐ and γ‐ENaC but not α‐ENaC expression in the colons of IEC‐MR‐KO mice was consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 88%
“…The actions of the PPARγ agonist pioglitazone on the distal nephron strongly resemble the actions of aldosterone, which also exerts both, SGK1-independent direct [3] and SGK1-dependent indirect effects on ENaC expression and activity [1,10,13,29,34]. As part of a counter-regulation to the pioglitazone-induced volume retention, endogenous aldosterone levels were suppressed.…”
Section: Discussionmentioning
confidence: 96%
“…Previous work has examined kidney expression of ENaC in the rat (Renard et al 1995, Asher et al 1996, Escoubet et al 1997, Stokes & Sigmund 1998, with modest upregulation of ENaC being reported. However, mineralocorticoid doses used in those rat studies were largely in the pharmacological range (5-to 15-fold greater) (Renard et al 1995, Asher et al 1996, Stokes & Sigmund 1998. In the present study, an upregulation of the level of ENaC mRNA of equal degree was seen across physiological changes in circulating aldosterone.…”
Section: Discussionmentioning
confidence: 99%